Haematoretinal barrier reaction on combined exposure of ionizing radiationand bright light - A. V. Potapov; Ye. Yu. Varakuta; S. V. Logvinov; A. A. Zhdankina; Ye. P. Mikhoulya; Ye. Yu. Anikina (Бюллетень сибирской медицины, 2007)
The aim of this work was to determine character of modifying radiation influence on damages of haematoretinal barrier components which is caused by light. The study showed that preliminary total x-ray radiation (5 Gy) increases lightning damages (3 500 lx, on the 1-st, 2-nd, 7-th, 14-th, 30-th days) of haematoretinal barrier which manifest by decreased specific square of chorioideas open capillaries, by haemodynamic disorders, reactive and destructive changes of pigmental epithelium. Damages of haematoretinal barrier is of focal character and are mostly l expressed on the areas of retina with massive destruction of neurosensory cells.